Achieving the Control of Nonmetallic Inclusions Morphology and Orientation by Electric Current. Issue 3 (28th November 2019) - Yan, Longge; Zhang, Xinfang
Abstract : The evolution of inclusions in electric field is investigated using numerical calculations. Due to electric current bypassing the inclusions, the electric current streamlines are not uniformly distributed but concentrated and distorted around inclusions. This abnormal electric current distribution causes an interaction force of adjacent inclusions, which is determined by the distance and orientation of the inclusions. The interaction force has three effects on the inclusions, i.e., attraction, repulsion, and rotation. The influence of three effects on the morphology, orientation, and distribution of inclusions is discussed. As a result, the inclusions evolve into a chain‐like structure aligned with the current direction, and inclusions separate from each other causing dispersion in the perpendicular direction. The evolution of the inclusions obeys the rule that the improvement of material conductivity reduces the electric free energy. The numerical calculation results are consistent with the experimental phenomena. Abstract : Pulsed electric current is applied to a system consisting of two adjacent nonmetallic inclusions and a metal liquid. The distorted electric current distribution around inclusions causes an interaction force, which causes changes in the morphology, orientation, and distribution of the inclusions. The numerical calculation results are consistent with the experiment.